ENHANCING THE ABILITY OF MATHEMATICAL REASONING WITH THE METHOD OF DISCOVERY GUIDED AT SMAN 23 BANDUNG INDEFINED INTEGRAL MATERIAL - Djatmiko Djatmiko; Ibrahim Akhid ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
The purpose of this study was to improve students' mathematical reasoning abilities through a guided training approach. This type of research is Class Action Research (CAR). The subjects of this study were students of class XI MIPA 3 SMAN 23 Bandung Academic Year 2018-2019 which amounted to 36 students. The method of data collection is done through a method of testing students' mathematical reasoning abilities.Data analysis techniques use methods that include data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate an increase in students' mathematical reasoning abilities. This can be seen through the percentage of learning completeness (fulfilling KKM = 70) in each cycle, namely cycle I by 53%, increasing in cycle II by 92%, and increasing again in cycle III by 100%.The conclusion of this study is that the guided training approach can improve mathematical reasoning abilities of class XI MIPA 3 SMAN 23 Bandung Academic Year 2018-2019.